SUCCESSFUL MANAGEMENT OF DYSTOCIA IN HOLSTEIN FRIESIAN COW DUE TO HYDROCEPHALIC FETUS (CONGENITAL ANOMALY) – A CASE REPORT - ARUNPANDIAN, J; N, SRIVASTAVA; B, NEETHU; KUJUR, ANJU; M, GANESAN (The Indian Journal of Animal Reproduction, 2021)
Hydrocephalus is a congenital condition caused by excessive accumulation of cerebrospinal fluid in the cranialcavity and this condition is reported less frequently in mammals. A 6 year-old Holstein Friesian cow was presentedwith the history of straining for 15 hours with rupture of water bag, but failure in expulsion of foetus. Per vaginalexamination revealed hydrocephalic foetus without corneal and pedal reflex. This case was diagnosed as dystociadue to hydrocephalus condition in the foetus. The dystocia was relieved manually by evacuating the fluid by incisingaround the head region followed by application of traction force. Thereafter the animal was treated for three days withfluid therapy, broad spectrum antibiotic and anti-inflammatory drugs.
Keywords: Hydrocephalus; fetus; dystocia; Holstein Friesian; cerebrospinal fluid